Effect of a Web-Based Guided Self-Help Intervention for Prevention of Major Depression in Adults With Subthreshold Depression: A Randomized Clinical Trial. Issue 9 (September 2016) - Buntrock, Claudia; Ebert, David Daniel; Lehr, Dirk; Smit, Filip; Riper, Heleen; Berking, Matthias; Cuijpers, Pim
Abstract : (Abstracted from JAMA 2016;315(17):1854–1863) Major depressive disorder (MDD) is associated with substantial disease burden and economic costs. Evidence-based treatments for this highly prevalent condition have not had much success in improving functional and health outcomes and it is estimated that only one third of the disease burden attributable to MDD could be averted.